Solvent polarity tuning to enhance the crystallinity of 2D-covalent organic frameworks for visible-light-driven hydrogen generation. Issue 23 (28th March 2022) - Elewa, Ahmed M.; EL-Mahdy, Ahmed F. M.; Hassan, Ahmed E.; Wen, Zhenhai; Jayakumar, Jayachandran; Lee, Tsung-Lin; Ting, Li-Yu; Mekhemer, Islam M. A.; Huang, Tse-Fu; Elsayed, Mohamed Hammad; Chang, Chih-Li; Lin, Wei-Cheng; et al.
Abstract : The higher the polarity or the hydrogen bond donor ability of the solvent, the more easily COFs crystallize, and the higher the COF crystallization, the higher the photocatalytic H2 evolution. Abstract : The fabrication of crystalline COF materials with predictable structures and desirable features is one of the crystal engineering strategic goals. Many synthetic factors play an invisible role in the crystallization of COFs, and the nature of the solvent is one of the most influential. Herein, we synthesized two series of benzothiadiazole-based COFs using three pairs of solvent systems of different polarities to explore the effect on the COF synthesis product crystallization, as well as the photocatalytic performance of H2 evolution under visible light irradiation. The results showed that the crystallinity of the COFs increases with increasing solvent polarity. This work showed that increasing the solvent polarity not only enhanced the crystallinity, but also enhanced the thermal stability and gave highly crystalline COFs with a shorter reaction time (30 min). More interestingly, the amorphous materials generated by the use of less solvent polarity (dioxane) can be transferred into crystalline COFs by increasing the polarity of the solvent with butanol or ethanol. The high crystallinity COFs exhibited excellent hydrogen evolution rates. Therefore, this work demonstrates that the choice of solvent is very important.